Akal dan Qalb dalam Perspektif Al Quran dan Neurosains - NurJannah NurJannah; Suyadi Suyadi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
So far, reason according to the Qur'an and Neuroscience is something that considers identity different, while neuroscience is the same entity. This study aims to analyze the mind and heart according to the perspective of Al-Quran and Neuroscience. This research approach is a qualitative type of literature. The data source of this research is a literature review. The data collection technique was carried out by searching for references in the google scholar data base through the keywords reason, qalb, al-quran and neuroscience. The collected data is then analyzed qualitatively by using a pattern of inductive and deductive thinking techniques. The results showed that the mind and qalb are functions of the brain, especially the frontal cortex and limbic system.